09.00 Saved by the skin of his teeth: a job well done!. Issue 12 (14th November 2019) - Jaffer, Fatima; Sibtain, Naomi; Holmes, Paul
Abstract : A 31-year-old former Game Ranger from South Africa presented with subacute onset parieto-occipital headache, photophobia, and vomiting, followed by diplopia, bradykinesia and progressive unsteadiness. There was a history of neonatal eczema, recurrent skin abscesses, osteomyelitis, tuberculosis, hepatitis A, and Rickettsia. On examination he had meningism, papilloedema, bilateral sixth nerve palsies, left lower motor neurone facial weakness and left upper limb pyramidal weakness. He was areflexic with normal sensation. Mild bilateral extrapyramidal signs, postural instability and gait initiation failure were observed. During admission, he developed acute left lumbar polyradiculopathy. Deep set eyes, coarse facial features, bony deformities, and retention of primary teeth were noted on examination. MRI showed bilateral globus pallidus necrosis, basal leptomeningeal enhancement, and multilevel lumbar root thickening and enhancement. CSF culture confirmed Cryptococcus gattii infection and an apical lung opacity seen on chest x-ray was consistent with a cryptococcoma. Twelve months of antifungal therapy was commenced with full symptom resolution. HIV was negative. Immunological tests revealed elevated IgE levels and IL-17 deficiency. A de novo mutation in the STAT3 gene (c.1241G>C; p.Arg414Thr) confirmed the diagnosis of autosomal dominant Hyperimmunoglobulin E (Job's) syndrome. We discuss Job's syndrome, the challenges in managing cryptococcal infection and immunological testing in non-HIV patients.